CO2 Capture by Using a Membrane-absorption Hybrid Process in the Nature Gas Combined Cycle Power Plants - Wenfeng Dong; Mengxiang Fang; Tao Wang; Fei Liu; Ningtong Yi (Aerosol and Air Quality Research)
Abstract This study’s main objective was to optimize the design parameters of the hybrid membrane-absorption CO2-capture process in natural gas steam cycle (NGCC) power plants. To calculate the CO2 concentration in the permeating gas and the required area for the separating membrane, a mass transfer model of a membrane for separating CO2, N2 and H2O was developed in Aspen Plus. The effects of the CO2 recovery rate of the membrane, the ratio of the feed gas pressure to the permeating-side gas pressure and the flow rate of the flue gas on the required area for the membrane, the power consumption of the compressor and the heat duty for the solvent regeneration were then analyzed. The optimal feed-gas-to-permeating-side-gas pressure ratio and the flue gas flow rate were found to be 10:1 and 50%, respectively. Furthermore, compared to traditional chemical absorption, the solvent regeneration’s heat duty decreased by more than 20.7% when the gas flow rate and the CO2 recovery rate were 100% and 20%, respectively.